Snell's clinical anatomy by regions - Wineski, Lawrence E.; Snell, Richard S. (Philadelphia : Wolters Kluwer, 2019)
"This book provides health science students a review of basic anatomy in a strong clinical context. The book is heavily illustrated. Most figures have been kept simple in order to convey the fundamental floor plans that underlie the organization of body regions. Illustrations summarizing the nerve and blood supply of regions have been retained, as have overviews of the distribution of cranial nerves"--Provided by publisher.
South Asian edition.
Includes index.
Preceded by Clinical anatomy by regions / Richard S. Snell. 9th ed. c2012.
Keywords: Body Regions -- anatomy & histology; Anatomy, Regional